„Uwspólnione” tworzenie sensu w interakcji dziecka z dorosłym - Monika Wiśniewska-Kin (Problemy Wczesnej Edukacji)
This article demonstrates the results of the educational project “stimulating children’s thinking” carried out in some primary schools in a metropolitan environment (Lodz, Poland). The aim of the study was to identify the ways of understanding the concept of community by 9–10-year old children. In the didactical intervention operations designed, the research data came from participated observation, focus interview, and children’s production analysis (graphical visualization, pairedassociate learning tasks and tests of unfinished tasks). Based on my research, I see the need for triggering the cognitive activity of pupils in conditions that ensure the development of conceptual systems. Moreover, the findings suggest the need of broader understanding of educational environments in Polish educational culture.